Xenopus laevis neural stem progenitor cells exhibit a transient metabolic shift toward glycolysis during spinal cord regeneration - Slater, Paula G.; Domínguez-Romero, Miguel E.; Campos, Guillermo; Aravena, Vania; Cavieres-Lepe, Javier; Eisner, Verónica (Frontiers in Cell and Developmental Biology, 2025)
Spinal cord injury (SCI) results in severe disruption of communication between the brain and body, causing motor, sensory, and autonomic dysfunctions. While SCI in mammals leads to permanent impairment due to limited regenerative capacity, certain non-mammalian species, such as Xenopus laevis larval stages, exhibit remarkable regenerative abilities. During Xenopus laevis spinal cord regeneration, neural stem precursor cells (NSPCs) surrounding the central canal rapidly proliferate in response to SCI, compensating for cellular loss, restoring canal continuity, and generating new neurons to reestablish lost connections. It has been described that mitochondria and cellular metabolism play essential roles in stem cell proliferation, self-renewal, and differentiation. However, the mitochondrial and cellular metabolic response during spinal cord regeneration remains unexplored. This study uses electron and confocal microscopy to investigate the NSPCs mitochondrial response in Xenopus laevis following SCI. We observed that mitochondria exhibit a rapid and transient response after SCI, characterized by a disruption of the mitochondrial localization, a decrease in mitochondrial number per cell section, and an increase in mitochondrial area and circularity. Furthermore, mitochondria adopted a swollen phenotype, which did not impair mitochondrial function or cellular energy balance. This morphological shift was accompanied by a transient decrease in the mitochondrial membrane potential and a metabolic switch favoring glycolysis. Therefore, these findings demonstrate that a transient metabolic shift toward glycolysis occurs during spinal cord regeneration.